2017
DOI: 10.1371/journal.pone.0169805
|View full text |Cite
|
Sign up to set email alerts
|

Novel Analysis of Immune Cells from Nasal Microbiopsy Demonstrates Reliable, Reproducible Data for Immune Populations, and Superior Cytokine Detection Compared to Nasal Wash

Abstract: The morbidity and mortality related to respiratory tract diseases is enormous, with hundreds of millions of individuals afflicted and four million people dying each year. Understanding the immunological processes in the mucosa that govern outcome following pathogenic encounter could lead to novel therapies. There is a need to study responses at mucosal surfaces in humans for two reasons: (i) Immunological findings in mice, or other animals, often fail to translate to humans. (ii) Compartmentalization of the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(85 citation statements)
references
References 26 publications
2
80
2
Order By: Relevance
“…These results may reflect the compartmentalised nature of the immune system, where circulating blood and the nasal mucosa have a different cellular composition and biological roles. Jochems et al [10] have previ- ously compared immune cell populations and cytokine profiles in blood samples to nasal mucosal samples from healthy adults and reported that immune cells collected from the nose differed in composition and activation state than those in blood. In AR sufferers, nasal washing and brushing samples typically yield epithelial cells along with infiltrating immune cells such as eosinophils, neutrophils, and basophils [11][12][13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results may reflect the compartmentalised nature of the immune system, where circulating blood and the nasal mucosa have a different cellular composition and biological roles. Jochems et al [10] have previ- ously compared immune cell populations and cytokine profiles in blood samples to nasal mucosal samples from healthy adults and reported that immune cells collected from the nose differed in composition and activation state than those in blood. In AR sufferers, nasal washing and brushing samples typically yield epithelial cells along with infiltrating immune cells such as eosinophils, neutrophils, and basophils [11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…In AR sufferers, nasal washing and brushing samples typically yield epithelial cells along with infiltrating immune cells such as eosinophils, neutrophils, and basophils [11][12][13]. In contrast to nasal mucosal samples, blood samples to do not contain epithelial cells and are more abundant in natural killer cells and monocytes [10,14]. Compared to the heat map analysis, additional insight into the pathogenesis of AR was gained when highly expressed genes were grouped into functional pathways.…”
Section: Discussionmentioning
confidence: 99%
“…In mouse models, acquisition of the organism leads to a mild acute inflammatory response in the URT that is ineffective at completely clearing the organism 67 . By contrast, preexisting inflammation is the most closely associated susceptibility factor in the human challenge model 68 . Many of the factors contributing to the eventual clearance of S. pneumoniae have been delineated.…”
Section: Colonization By S Pneumoniaementioning
confidence: 94%
“…Pneumococcal biofilm structures have been detected in biopsy samples from patients with otitis media 109 and in the middle ear cleft of chinchillas co-infected with S. pneumoniae and Haemophilus influenzae 110 . In biopsy samples from volunteers colonized in experimental human studies, S. pneumoniae was found in microcolonies 68 , although it has not been determined whether these have characteristics of biofilms, such as an extracellular matrix. The production of an extracellular matrix has a major impact on the ability of S. pneumoniae that has been grown in a biofilm in vitro to subsequently translocate from the nasopharynx to the lungs in a murine infection model 111 .…”
Section: Invasive Pneumococcal Diseasementioning
confidence: 99%
“…The serum is harvested from bovine foetuses taken from pregnant cows during slaughter [47]. Irradiation of FBS is frequently used to eliminate live virus, but no process can be guaranteed as fully effective over time [48].…”
Section: Culture Processmentioning
confidence: 99%